A transformational change in scintigraphic gastroesophageal reflux studies: A comparison with historic techniques. (29th November 2020) - Burton, Leticia; Joffe, David; Mackey, Douglas W; Van der Wall, Hans; Falk, Gregory L
Abstract: Background: The inclusion of scintigraphy in the diagnostic algorithm for gastroesophageal reflux is controversial due to variability in methodology and reporting. A novel scintigraphic reflux study has been developed and validated against the current standards for the diagnosis of gastroesophageal reflux disease (GORD). Objective: To compare a new scintigraphic reflux test against historic techniques and standardised diagnostic reference tests for gastroesophageal reflux disease. Methods: Paired scintigraphic studies were conducted in seventeen patients. All patients underwent at least one other standardised diagnostic reflux test such as 24‐ hour oesophageal impedance/ pH, and oesophageal manometry, barium swallow, gastroscopy or the Peptest. Patients inadvertently presented at sites B for scintigraphic reflux testing rather than at Site A which was part of an approved study. The findings from sites B did not correlate with clinical symptoms and other diagnostic reference tests from GORD. These studies were then repeated at Site A with approval from the patients. A second reflux study was performed at site A, utilising a novel technique with the capability of assessing oesophageal and extra‐oesophageal disease. Results: The Site A technique shows good concordance with the reference diagnostic tests with an accuracy of 82.4% and kappa of 0.64 (SE: 0.16, p = 0.00). Site B had an overall accuracy of 47.1% and kappa of 0.066 (SE: 0.068, p = 0.45). Conclusion: The Site A technique shows higher accuracy than either site B or the historic reflux techniques. It has characteristics that make it an effective screening tool for assessment of local oesophageal disease and its extraoesophageal manifestations.